Aktivitas Antibakteri Dan Antifungi Ekstrak Etanol Daun Nyireh (Xylocarpus Granatum J. Koenig) - Suci Fitriani Sammulia; Suhaera Suhaera; Henny Rachdianti Tjahjono Suyarto; Arie Vonikartika; Yustika Sandey Margaretha (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Nyireh plant (Xylocarpus granatum J. Koenig) is a mangrove plant that can usually grow in tidal areas, river embankments, and along rivers. This plant is believed to be a traditional medicine in dealing with diarrhea disorders, wound cleansers and sun protectors. This study aims to determine the antibacterial and antifungal activity of the ethanol extract of nyireh leaves against Pseudomonas aeruginosa, Sthapylococcus aureus and Candida albicans fungi. Nyireh leaf extract was prepared using the maceration method with 70% ethanol solvent. In testing the antibacterial and antifungal activity using the disc diffusion method with a concentration of 2%, 4%, 6%, positive control for bacteria (Tetracycline) positive control for fungi (Ketoconazole) and negative control (DMSO 5%). Research on the antibacterial and antifungal activity test of ethanol extract of nyireh leaves produced a strong inhibitory power at a concentration of 6%. In Pseudomonas aeruginosa bacteria concentration of 6% with an average concentration of 17.05 mm, Sthapylococcus aureus bacteria with an average concentration of 6% with an average of 22.95 mm and Candida albicans fungi at a concentration of 6% with an average of 11.88 mm. Potential as antibacterial and antifungal against the bacteria Pseudomonas aeruginosa, Sthapylococcus aureus and the fungus Candida albicans.